If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = -2(x)(x) + 3 Multiply x * x 4 = -2x2 + 3 Reorder the terms: 4 = 3 + -2x2 Solving 4 = 3 + -2x2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x2' to each side of the equation. 4 + 2x2 = 3 + -2x2 + 2x2 Combine like terms: -2x2 + 2x2 = 0 4 + 2x2 = 3 + 0 4 + 2x2 = 3 Add '-4' to each side of the equation. 4 + -4 + 2x2 = 3 + -4 Combine like terms: 4 + -4 = 0 0 + 2x2 = 3 + -4 2x2 = 3 + -4 Combine like terms: 3 + -4 = -1 2x2 = -1 Divide each side by '2'. x2 = -0.5 Simplifying x2 = -0.5 Reorder the terms: 0.5 + x2 = -0.5 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.5 + x2 = 0.0 The solution to this equation could not be determined.
| 10a+8(a-3)=15 | | 4=-2x+3 | | 2x+40-4x=1-7x+4 | | 1205(2w-13)=3(2w-5) | | 2ab*3+3xb*2-5b*4+2b*2= | | csquared-5c=0 | | 5n+6n^4-7n+15n^4+13n=x | | (5x-8)(x^2+9x-10)= | | 3x^4+12x^3-36x^2=0 | | 1.4-0.2x=3.2 | | 0.07+0.4x=2 | | 5n-1=2n+8 | | 3b-9-86=11 | | -3p+2=2p+12 | | 3x^1+12x=0 | | 8lx-9l+8=32 | | 4m+7=9m-3 | | 2.4=4.2 | | 1008/48 | | 3(9-8x)+8(3x+4)=11 | | 5x-2y+20=0 | | 10-(4x-5)=6-5x | | 4w-16=12+3w | | 5w-2(w-18)=7w-15 | | (x+1)/(x-3)-3/5=4/(x-3) | | 2d^2+12d/d+6 | | 4x+5=3(x+15) | | x(3x-2)+x(4x-5)=(7x+4)(x-1) | | x+1/x-3-3/5=4/x-3 | | 3.7x-1.9=-9.3 | | 12x-8+3x-4=11x-2+3x | | 5b-20=10b+5 |